Effects of the hydroxyurea derivative 1,3,4-thiadiazoles on antioxidant vitamins and MDA in serums of rats and cell viability of MCF-7 breast cancer cells - Karagozoglu, Yusuf; Alayunt, Naci Omer; Karatepe, Mustafa (Society of Cell Membranes and Free Oxygen Radicals, 2015)
In this study, the effects of as used ligand [1-hydroxy - 2 - (5 - (trifluoromethyl) - 1, 3,4-thiadiazole-2 - yl) guanidine] and its Mn, Cd, Cr complexes on the antioxidant vitamins and MDA levels in the serums of rats and antitumor activity of these chemical compounds on the MCF-7 breast cancer cells at different concentrations were investigated. When the results were compared between the levels of control and experimental groups of antioxidant vitamins and MDA statistically, it was observed that there were decreased levels of A, E, and C vitamins in groups of applied Cd (II) and Cr (II) complexes compared with the control group, whereas MDA levels were increased. The antioxidant vitamins and MDA levels in serum were determined by HPLC. It was clearly observed that the subcutaneously MCF-7 breast cancer cells treated Ligand (L), Mn (L) 2, Cd (L) 2 and Cr (L) 2 complexes had the low levels of cell viability activity when compared to the untreated control cells clearly increased according to the control group for after incubation 24 h onwards to 48 h. Cell vialities measured by electronic microscope. As a result, it suggested that thiadiazole compounds exhibit antitumor activity with reduction in serum antioxidant vitamins of rats can cause cytotoxic effect depending on the mechanism of oxidative damage.
Keywords: 1,3,4-thiadiazole; Antioxidant; Antitumor; Hydroxyurea